Tindak Tutur Ekspresif Keluhan dalam Drama Korea “My Liberation Notes” - Anjani, Shofi Hawa; Rosyadi, Alfiana Amrin (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2024)
This article discusses the complaint speech acts found in the dialogues of “My Liberation Notes” drama. This study aimed to identify strategies and linguistic features of each complaint speech act found in the drama. The collected data were analyzed with qualitative descriptive method using Kim Kyung-Ryung’s theory by classifying data in six complaint speech act strategies that appeared in the dialogues. Each strategy and sub-strategy had different linguistic features such as a variety of the words, grammars, sentence types, expressions, etc. 암시하기(amsihagi)/hints strategy used question form sentence and expression of carefulness, 질책하기 (jilchaekhagi)/rebuking used expression of surprise, 비난하기 (binanhagi)/criticism used form of negation, 짜증나기 (jjajeungnagi)/annoyance used interjection and word with annoying meaning, 내적수식어 (naejeoksusikeo)/internal modification used expression and word that highlight politeness, and 외적수식어 (wejeoksusikeo)/external modification appeared with usage of word and expression that weaken and strengthen the meaning of the action.